Education of Herbal Soap Homemade in Dukuh Kertan, Sumberagung, Bantul: Edukasi Pembuatan Sabun Herbal di Dukuh Kertan, Sumberagung, Bantul - Arifah, Mitsalina Fildzah; Shalahuddin Al Madury; Nurul Afniatun; Citra Eka Runenti (Dinamisia : Jurnal Pengabdian Kepada Masyarakat, 2025)
Herbal soap is the saponification process of natural ingredients from medicinal plants. Herbal ingredients are minimally unknown by the people of Pedukuhan Kertan to make natural cosmetics. Herbal soap is successful in being environmentally friendly, safe against detergent allergies, and increasing the economic value of herbal ingredients in the community. Education in making herbal soap was needed for the people of Dukuh Kertan, Sumberagung, and Bantul in 2024 to implement health promotion through community empowerment. Community service activities were determined using direct counseling and training methods. The community service targeted Family Welfare Empowerment (PKK) and Youth organization in Dukuh Kertan. The series of activities began with counseling on education on making herbal soap, practical training, and competitions between community groups in each RT with various variations of materials according to creativity. Community service evaluations were carried out in the form of a pretest and posttest carried out by 27 people. The results of the pretest on community knowledge of herbal soap were 13 (excellent), 6(understand), 4 (quite knowledgeable), 2 (less knowledgeable), and two people (ignorant). The knowledge of participants in the posttest increased by 24 (excellent), 2 (understand), and one people (quite knowledgeable). Herbal soap could display the creativity of each group of the community. Therefore, making herbal soap could increase knowledge and skills of herbal soap products through community empowerment.